Immunoglobulin E-Dependent Activation of Immune Cells in Rhinovirus-Induced Asthma Exacerbation - Kawakami, Toshiaki; Kasakura, Kazumi; Kawakami, Yu; Ando, Tomoaki (Frontiers in Allergy, 2022)
Acute exacerbation is the major cause of asthma morbidity, mortality, and health-care costs. Respiratory viral infections, particularly rhinovirus (RV) infections, are associated with the majority of asthma exacerbations. The risk for bronchoconstriction with RV is associated with allergic sensitization and type 2 airway inflammation. The efficacy of the humanized anti-IgE monoclonal antibody omalizumab in treating asthma and reducing the frequency and severity of RV-induced asthma exacerbation is well-known. Despite these clinical data, mechanistic details of omalizumab's effects on RV-induced asthma exacerbation have not been well-defined for years due to the lack of appropriate animal models. In this Perspective, we discuss potential IgE-dependent roles of mast cells and dendritic cells in asthma exacerbations.